Travels and mobilities in the Middle Ages: from the Atlantic to the Black Sea - O'Doherty, Marianne; Schmieder, Felicitas (International medieval research, 2015)
Part I. Centres and Peripheries: Travellers to and on the Margins. 'Them Friars Dash About': Mendicant Terminario in Medieval Scandinavia / Johnny Grandjean Gøgsig Jakobsen -- Papal Delegations to the Edge of the World: Visits from the Papal Curia to Norway Between 1050 and 1536 / Sæbjørg Walaker Nordeide -- From the Edge of Europe to Global Empire: Portuguese Medicine Abroad (Thirteenth to Sixteenth Centuries) / Iona McCleery -- Have Crutch, Will Travel: Disabled People on the Move in Medieval Europe / Irina Metzler -- Part II. Nobility of the Road: Travel and Status. Why Didn't King Stephen Crusade? / John D. Hosler -- The Travels of Ivan Babonić: The Mobility of Slavonian Noblemen in the Fourteenth Century / Hrvoje Kekez -- The Perfect Gentle Knight: Fourteenth-Century Crusaders in Prussia / Mary Fischer -- Part III. Men and Women on the Move: Gendered Mobilities. Dangerous Travellers: Identity, Profession, and Gender Among the German Landsknechts (1450-1570) / Stefanie Rüther -- On the Road Again: The Semi-Nomadic Career of Yolande of Aragon (1400-1439) / Zita Rohr -- Student Mobilities and Masculinities: The Case of the Empire North of the Alps in the Fifteenth Century / Maximilian Schuh -- Part IV. Migration and Return: Peoples and Objects on the Move. Slavs but not Slaves: Slavic Migrations to Southern Italy in the Early and High Middle Ages / Zrinka Nikolić Jakus -- Ex partibus orientalibus translata ad hanc urbem: The Evacuation of Elements of Church Decoration from Pera to Genoa in 1461 / Rafał Quirini-Popławski -- A Herald and his Objects in Exile: Roger Machado and his Memorandum Book, 1484-1485 / Gemma L. Watson
Keywords: Europe -- Description and travel; Konferenzschrift -- 2010 -- Leed; Aufsatzsammlung; Geschichte 600-1570; Mobilität; Reise; Europa